Предмет: Алгебра,
автор: crystal99
как решить уравнение (2х+1)(х-4)=(х-2)(х+2)
Ответы
Автор ответа:
0
(2х+1)(х-4)=(х-2)(х+2),
2х²-8х+х-4=х²-4,
2х²-8х+х=х²,
2х²-7х=х²,
2х²-7х-х²=0,
х(2х-7-х)=0,
х(х-7)=0,
х=0. х-7=0,
х=0+7,
х=7.
Ответ: 0, 7.
2х²-8х+х-4=х²-4,
2х²-8х+х=х²,
2х²-7х=х²,
2х²-7х-х²=0,
х(2х-7-х)=0,
х(х-7)=0,
х=0. х-7=0,
х=0+7,
х=7.
Ответ: 0, 7.
Автор ответа:
0
спасибки огромное!!!
Автор ответа:
0
пожалуйста
Похожие вопросы
Предмет: Окружающий мир,
автор: RENDIPOPING
Предмет: Қазақ тiлi,
автор: irinayarovaya78
Предмет: Химия,
автор: juliakitchenko200320
Предмет: Физика,
автор: DayanaVurst
Предмет: Литература,
автор: SYPER12345